2005
DOI: 10.1097/01.sap.0000141942.27182.55
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of High-Resolution Ultrasonographic Findings With the Clinical Symptoms and Electrodiagnostic Data in Carpal Tunnel Syndrome

Abstract: There are several different imaging methods that are helpful in the diagnosis of carpal tunnel syndrome, including traditional radiography, computed tomography (CT), and magnetic resonance imaging (MRI). CT and MRI offer the advantage of providing direct visualization of the structural abnormality of the carpal tunnel and median nerve, but both of these modalities are expensive and time-consuming. Recently, high-resolution ultrasonography has been reported to be effective in the study of the musculoskeletal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
74
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 11 publications
11
74
0
Order By: Relevance
“…Abicalaf et al 9 found an average decrease of 6.4 mm 2 (CI, 5.6 -7.2 mm 2 ) and Colak et al 10 reported an average decrease of 1.3 mm 2 (CI, 0.9 -1.6 mm 2 ). In contrast to the other studies, the work of Lee et al 11 reported a 2.0-mm 2 increase of the median nerve CSA (CI, 0.9 -3.0 mm 2 ). Our results lay between those reported by Abicalaf et al 9 and Lee et al 11 and are in accordance with those by Colak et al 10 Our CIs and those of the Colak et al 10 study do not overlap with the remaining 2, 9,11 indicating that results are not compatible.…”
Section: Discussionmentioning
confidence: 62%
“…Abicalaf et al 9 found an average decrease of 6.4 mm 2 (CI, 5.6 -7.2 mm 2 ) and Colak et al 10 reported an average decrease of 1.3 mm 2 (CI, 0.9 -1.6 mm 2 ). In contrast to the other studies, the work of Lee et al 11 reported a 2.0-mm 2 increase of the median nerve CSA (CI, 0.9 -3.0 mm 2 ). Our results lay between those reported by Abicalaf et al 9 and Lee et al 11 and are in accordance with those by Colak et al 10 Our CIs and those of the Colak et al 10 study do not overlap with the remaining 2, 9,11 indicating that results are not compatible.…”
Section: Discussionmentioning
confidence: 62%
“…In these instances imaging can play an important role in helping to define the site and etiology of nerve compression or in establishing an alternative diagnosis [2]. Hence, it has been widely reported that imaging modalities can feasibly demonstrate the causes and locations of NECS [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] Ultrasound imaging has been described to detect pathologies such as thickening of the flexor tendons 13 and transverse carpal ligament, 14 shape and echogenicity alterations, restricted median nerve sliding in the carpal tunnel, 15,16 synovial proliferation, soft-tissue infection and joint effusion, tissue calcification and tumors, 17 persistent median artery, 18 tendinous and ligamentous injuries and swelling of the median nerve in the proximal part of the carpal tunnel, and flattening of the median nerve in the distal part of the carpal tunnel. 6,14,[19][20][21] High-resolution ultrasonography with approximately 7 MHz transducers is suitable for assessment of dynamic changes in the tunnel. Ultrasonography is comparable in image quality to magnetic resonance imaging (MRI) and computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%